Trends in the overall survival rates in women with advanced ovarian cancer in a single tertiary centre in New Zealand. (9th October 2019) - Yeoh, Sara; Simcock, Bryony; Innes, Carrie; Mclachlan, Jennifer; Harker, Dianne; Sykes, Peter
Abstract : Background: Survival rates for women diagnosed with ovarian cancer are much poorer than other gynaecological cancers and greatly depend on stage at diagnosis. A recent publication showed that unlike some other developed countries, there has been no improvement in the five‐year survival rate for those diagnosed with ovarian cancer in New Zealand. Aim: To compare the five‐year survival rate of women diagnosed with advanced ovarian cancer in a single tertiary hospital during two 36‐month time periods 10 years apart. Materials and Methods: An observational retrospective review of patient clinical notes, including all women diagnosed with stage three or four ovarian cancer between 2000 and 2002 (Cohort 1) and 2010–2012 (Cohort 2). Eligible patients were identified through the Regional Gynaecology Oncology database. Clinical notes were reviewed to compare the five‐year survival rate between these two time periods and look at changes in patterns of care over time. Results: Eighty‐three women were diagnosed in 2000–2002 and 125 women in 2010–2012. There was no difference in five‐year survival between cohorts (21.7% vs 23.2%, P = 0.80). Mean age at diagnosis did not differ between cohorts (62.1 years vs 63.5 years, P = 0.43); however, there were more women with stage four cancer in Cohort 2 (14% vs 30%, P = 0.01). In Cohort 2, more women were treated with neoadjuvant chemotherapy (20% vs 34%, P = 0.04) or chemotherapy only (6% vs 18%, P = 0.01). Conclusion: Five‐year overall survival in women diagnosed with advanced ovarian cancer in our centre has not changed over the last 10 years.